2022
DOI: 10.1002/adma.202207172
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limit of Open‐Circuit Voltage Deficit via Modifying Buried Interface in CsPbI3 Perovskite Solar Cells

Abstract: harmful phase separation behavior, which makes it the most prominent candidate for high-efficiency single-junction cells or sub-cell absorbers in tandem cells. [1,2] It has witnessed tremendous progress in inorganic CsPbI 3 -based perovskite solar cells (PSCs) under unremitting efforts over the past few years, especially on stabilizing photo-active black phase and improving perovskite crystal quality. [3][4][5] However, the power conversion efficiency (PCE) of CsPbI 3 -based PSCs still remains inferior to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Since the short-circuit current (J SC ) of inorganic PSCs has almost approached its S-Q limit by tuning the composition [37][38][39] and processing methods [34,40,41,42] of the perovskite film, interfacial modification has become considerably necessary to ensure further advances in device performance, including open-circuit voltage (V OC ), fill factor (FF), hysteresis, and stability/reliability. It is because the interface is closely correlated with surface defects, energy level alignment and environmental contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the short-circuit current (J SC ) of inorganic PSCs has almost approached its S-Q limit by tuning the composition [37][38][39] and processing methods [34,40,41,42] of the perovskite film, interfacial modification has become considerably necessary to ensure further advances in device performance, including open-circuit voltage (V OC ), fill factor (FF), hysteresis, and stability/reliability. It is because the interface is closely correlated with surface defects, energy level alignment and environmental contact.…”
Section: Introductionmentioning
confidence: 99%
“…It is because the interface is closely correlated with surface defects, energy level alignment and environmental contact. [43][44][45] Zhu et al reported that the oxidized Ti 3 C 2 T x MXene (OMXene) nanoplates on CsPbI 3 film can provide a physical barrier against moisture and improve charge separation at the perovskite-electron-transport layer (ETL) interface via an enhanced electric field. Consequently, CsPbI 3 /OMXene-based inverted devices demonstrated a 19.69% PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Although several strategies and efforts have been made to optimize the fabrication of PQDs, there is still room to reduce the voltage loss in 1. [2][3][4][70][71][72][73][74][75][76] PQDSCs based on the whole device level. In Fig.…”
Section: Non-radiative Recombination In Pqdscsmentioning
confidence: 99%
“…Schematic illustration of (b) voltage loss with respect to the bandgap for bulk PSCs and (c) voltage loss with respect to bandgap for PQDSCs. The plots are based on the data listed in Table1 [2][3][4][70][71][72][73][74][75][76].…”
mentioning
confidence: 99%
“…Among the aforementioned methodologies, additive engineering is considered the most effective and promising option because of the well-established intrinsic coordination ability of lead cations in the [PbI 6 ] 4– octahedral matrix of perovskites. The unique polar characteristics of lead cations allow them to function as Lewis acids that can undergo coordinative bonding with numerous types of dopant molecular bases and perovskites. Thus, a large diversity of additives and their functions, ranging from small molecules to polymers, can be exploited in improving the properties of perovskite films. Song et al proposed incorporating a poly­(styrene- co -butadiene) (SBS)-polyurethane (PU) composite into perovskites to facilitate crystal-orientated growth, thereby achieving excellent bending and stretching stability in related devices.…”
mentioning
confidence: 99%